Trend Terminologi Hari Santri di Media Sosial Pada Era Generasi Milenial - Wahyudin, Wahyudin; Silahuddin, Silahuddin; Bin Has, Qoiz Azizah (Ri'ayah: Jurnal Sosial dan Keagamaan, 2024)
The state's role in establishing Islamic boarding school days has so far been carried out through formal institutions, but basically, Islamic boarding schools have inherent forms of teaching and are a system of resilience in life. The trend of santri days has become a fundamental form of religious teaching used by Islamic boarding schools in Indonesia. The study in this paper starts from argument. Students in several Islamic boarding schools will face limited access and understanding of modern technology and information. On the other hand, they will face social challenges such as adaptation to the Islamic boarding school environment, cultural differences, or conflicts between students. In some Islamic boarding schools, some students may face stigma or negative stereotypes from society. The analytical approach method uses phenomenology. By using phenomenological analysis of observation and documentation data. This study found that the religious doctrines adhered to by each Islamic boarding school are the foundation for overcoming life's problems. The existence of Kyai figures, government figures and ustads who uphold these fundamentals means that the problems that occur can be resolved. Kyai figures who in this research also have a position as religious elites have relevant functions in playing socialization, integration, normative functions, and as social control so that problems can be resolved. The use of the concept of trend terminology in this article successfully shows that santri day is a form of mechanism in forming the millennial generation in overcoming socio-religious problems in Indonesia.